Rumusan Pendidikan Tentang Hukum Islam dan Hukum Adat - Rudi Hartono (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2018)
In the formulation of education about law, especially Islamic law, including maritime law in Indonesia, there was a fierce debate between legal experts about the status of customary law. Therefore, three (3) arise regarding the relationship of Islamic law with customary law, namely: the theory of receptio a contrario in complexu, and receptie theory. The validity of Islamic inheritance law in Indonesia is not through the theory of receptio in complexu and the theory of receptie but the Islamic inheritance law that applies because of the position of Islamic law itself. In addition to the theory of receptio a contrario mentioned above, the formulation of legal lines is also used in the laws and Complications of Islamic Law, the Qur'an's Hadith of the Prophet, and the opinions of the Companions of the Prophet and Islamic jurists.